Clinical characteristics and short-term outcomes of children with severe acute respiratory syndrome coronavirus 2-associated multisystem inflammatory syndrome treated with methylprednisolone and/or intravenous immunoglobulin - Arora, Mansi; Kumar, Atul; Gupta, Aditi (International Journal of Contemporary Pediatrics, 2024)
In this case series, we evaluated the clinical profiles and short-term outcomes of four pediatric patients diagnosed with SARS-CoV-2-associated multisystem inflammatory syndrome (MIS-C), treated with Methylprednisolone and/or intravenous immunoglobulin (IVIg). All cases were managed at a tertiary care hospital in the Rohilkhand region and met the WHO diagnostic criteria for MIS-C. The study period spanned from May to December 2021, with the primary outcome being the resolution of fever. Secondary outcomes included the length of hospital stay, mortality, duration of respiratory or inotropic support (if applicable), and the time to normalization of inflammatory markers. The four cases presented with varying degrees of MIS-C involvement: two patients had significant cardiac involvement, one displayed neurological symptom, and another had systemic inflammatory manifestations. All patients received IVIg (2 g/kg) and Methylprednisolone (2 mg/kg/day). Fever resolved within 3-5 days of treatment, and inflammatory markers normalized within a median of 5 days. Two cases required inotropic support for shock, and one required high-flow nasal cannula (HFNC) oxygen for respiratory distress. No mortality was observed in this cohort. In conclusion, treatment with IVIg and Methylprednisolone was associated with favorable outcomes in these MIS-C cases.